The Correlation between Knowledge, Attitudes toward Occupational Safety and Health and Near Miss - Febrina Dewi Safitri; Noeroel Widajati (Universitas Airlangga, 2019)
Introduction: The results of the research conducted by Frank Bird concluded that every occupational safety and health is preceded by a near-injury occurrence or near miss. Near miss is an incidence that potentially causes loss, which is triggered by direct factors, namely unsafe action, and unsafe conditions, and basic factors, such as workers and works. The workers as a basic factor comprise their knowledge and attitudes towards occupational safety and health-related to personal protective equipment (PPE). Methods: This research is descriptive research that aims to identify the strength of the relationship between the knowledge and attitudes toward occupational safety and health that is related to PPE in the Outfitting Unit at PT. Dok dan Perkapalan Surabaya by applying the cross-sectional design. The data is obtained by questionnaire and interview. The questionnaire is distributed to all 30 workers in the Outfitting Unit at PT. Dok dan Perkapalan Surabaya. Results: Indicate that the majority of the workers experience a low-level of near-miss (90%), while the other 10% experience a moderate-level of near-miss. The correlation coefficient value as many as 0.149 denotes that there is a weak relationship between the workers’ knowledge of occupational safety and health and a near miss. Similarly, the relationship between the workers’ attitudes toward occupational safety and health regarding PPR and near-miss is also a weak relationship with the correlation coefficient value of 0.236. In conclusion, it is affirmed that effective communication between units and the provision of PPE are the factors that cause the occurrence of near-miss in the company. Keywords: attitude, knowledge, near miss